Scurvy: A New Old Cause of Skeletal Pain in Young Children - Chalouhi, Christel; Nicolas, Nayla; Vegas, Nancy; Matczak, Soraya; El Jurdi, Houmam; Boddaert, Nathalie; Abadie, Véronique (Frontiers in Pediatrics, 2020)
We report 3 cases of scurvy in children that occurred during a short period of time (2018) in a general pediatrics unit of a tertiary hospital for children in Paris. All the children were around 3 years of age and were admitted for skeletal pain and altered general state, which mimicked infectious or malignant diseases. Their selective diet was not the prominent issue. The diagnosis of scurvy was delayed, after too many unnecessary examinations and medications. Bone imaging (X-ray and MRI) was a posteriori considered typical, but lesions were not easily identified as scurvy lesions because scurvy is not well known by pediatricians and radiologists who should be mindful of this historical diagnosis.